Experimental evaluation of the out-of-plane behaviour of traditional stone masonry buildings in Azores, Portugal - Arêde, A. (2014)
Recent earthquakes around the world, particularly those that have recently occurred in the southern regions of Europe, have provoked extensive damages in many traditional masonry structures calling into question the preservation and the safeguard of this heritage. This fact has driven the concern of the scientific community which has been undertaking several studies focused on the seismic vulnerability assessment of this type of structures, particularly in view of their rehabilitation and seismic strengthening/retrofitting. In this context, this paper aims at presenting an in situ experimental test campaign recently carried out on an existing building abandoned after the 1998 Azores earthquake, in order to characterize the out-of-plane behavior of traditional masonry constructions. For testing purposes, an experimental test setup based on a self-equilibrated airbags system was used in the out-of-plane test of masonry piers under distinct conditions: original, retrofitted and strengthened. An overall and brief discussion is included concerning the used test setup, in order to highlight their advantages and shortcomings. The system was found to be efficient for in-situ out-of-plane testing of this type of thick (and massive) stone masonry walls, by applying distributed lateral loads which are agree better with actual inertia forces during seismic occurrence rather than top applied forces. The obtained results are presented and discussed focusing on the effectiveness of the retrofitting and/or strengthening solutions applied during the 1998 Azores reconstruction process. By comparing the results from the tested panels, such solutions were found to significantly increase the walls strength and energy dissipation capacity although not that much for the ultimate displacement.